ANALISIS POTENSI DAN PENETAPAN TARGET PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN - Novitasari, Novitasari; Fery, Irlan (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This research is intended to determine the potential and the determination of PBBP2 on local taxes. This study uses primary data obtained from interviews with the Head of the Sub-Sector for Registration, Data Collection, Assessment and Determination of PBB and BPHTB while the secondary data is the main data for PBB regulations and the realization of the main PBB provisions and Report Targets and realization of PBBP2 BPPRD revenues for Musi Banyuasin Regency from 2018 to 2022. The data analysis technique used is quantitative descriptive analysis. The technique is to calculate the ratio of the achievement of PBBP2 revenue targets and the main PBB provisions, the target ratio and the realization of PBBP2 revenues and present the data graphically. The results of this study indicate that the performance of BPPRD Musi Banyuasin Regency in collecting local taxes, especially PBBP2 is not optimal because the PBBP2 revenue target setting is not based on SPOP and is not in accordance with tax potential so that the PBBP2 target is not accurate. This had the impact of lowering the acceptance of the principal PBB provisions from PBBP2 of 74.91%, so that the realization of the PBBP2 target revenue with an average realization of 105.45%.